Gamification in Qur’anic Learning: Evidence from Muslim Students in Hybrid Classrooms - Amin, Syukri; Nurfadilla , Annisa; Rasman; Puspitasari , Amelia; N.Baskautshar (Cognoscere: Jurnal Komunikasi dan Media Pendidikan, 2023)
This study critically examines the application of gamification features—points, badges, and leaderboards—within hybrid Qur'anic learning environments, testing their influence on student motivation and learning outcomes through a Self-Determination Theory framework. Employing a quantitative approach with SmartPLS analysis on data from 250 Muslim students, the research yielded a critical paradox: while points and badges positively influenced engagement, leaderboards demonstrated a negative effect, and crucially, the resulting engagement failed to translate into improved Qur'anic learning effectiveness. The model's explanatory power was severely limited (R² = 0.021 for learning outcomes), and a fundamental measurement model failure was observed, with invalid reliability and validity metrics (e.g., negative Cronbach's Alpha). This comprehensive model invalidity challenges the direct transferability of secular gamification models to religious education, suggesting that extrinsic rewards may undermine intrinsic spiritual motivation. The study concludes that a paradigm shift is necessary, advocating for the development of a unique, theologically-grounded gamification pedagogy that prioritizes spiritual growth over competitive mechanics and calls for a fundamental reconceptualization of engagement metrics in sacred learning contexts.